2013
DOI: 10.1093/aje/kws317
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Group Sequential Methods to Observational Postlicensure Vaccine Safety Surveillance: Results of a Pentavalent Combination DTaP-IPV-Hib Vaccine Safety Study

Abstract: To address gaps in traditional postlicensure vaccine safety surveillance and to promote rapid signal identification, new prospective monitoring systems using large health-care database cohorts have been developed. We newly adapted clinical trial group sequential methods to this observational setting in an original safety study of a combination diphtheria and tetanus toxoids and acellular pertussis adsorbed (DTaP), inactivated poliovirus (IPV), and Haemophilus influenzae type b (Hib) conjugate vaccine (DTaP-IPV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 33 publications
1
46
0
1
Order By: Relevance
“…17,18 There is no evidence that the acellular DTaP vaccines in use since the late 1990s are associated with seizures in the United States. 31 Other infant vaccines currently in use, for instance the DTaP, inactivated poliovirus, and Haemophilus influenza type B combined vaccine (DTaP-IPV-HIB), have not been associated with seizures in the United States, 32 although DTaP-IPV-HIB has been linked with increased febrile seizures in Denmark. 24 Other early childhood vaccines that have been associated with febrile seizures in the United States include inactivated influenza vaccine, but only in some influenza seasons, such as 2010-2011, and the 13-valent pneumococcal conjugate vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 There is no evidence that the acellular DTaP vaccines in use since the late 1990s are associated with seizures in the United States. 31 Other infant vaccines currently in use, for instance the DTaP, inactivated poliovirus, and Haemophilus influenza type B combined vaccine (DTaP-IPV-HIB), have not been associated with seizures in the United States, 32 although DTaP-IPV-HIB has been linked with increased febrile seizures in Denmark. 24 Other early childhood vaccines that have been associated with febrile seizures in the United States include inactivated influenza vaccine, but only in some influenza seasons, such as 2010-2011, and the 13-valent pneumococcal conjugate vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Вак-цина включена в графики вакцинации детей различных стран мира (как на первом году жизни для первичной вакцинации, так и для ревакцинации на втором году). В многоцентровых исследованиях свойств пентавакци-ны доказана безопасность [5], хорошая переносимость и высокая иммуногенность препарата в отношении всех антигенов, включенных в его состав, при использовании разных графиков вакцинации [6,7].…”
Section: вопросы современной педиатрииunclassified
“…1); however, tolerance to the drug and vaccination with separate monocomponent vaccines depending on frequency of administration thereof (tb. 2) and generation of specific antibodies has been compared [6][7][8][9]. General safety of the pentavalent vaccine with acellular pertussis component has been evaluated in comparison with whole cell vaccine.…”
mentioning
confidence: 99%
“…Comparative studies of tolerance to the pentavalent vaccine in combination with a recombinant hepatitis B vaccine and to vaccination with inactivated poliovirus, acellular pertussis-diphtheria-tetanus vaccine and conjugate Hib vaccine (Hib) demonstrated equivalent tolerance to the immunization. Several studies [6,7,9] demonstrated immunogenicity of the pentavalent vaccine: protective antibody titer against diphtheria and tetanus (more than 0.01 IU/ml) developed in 92.2-100% of children after the primary vaccination, against type 1, 2 and 3 poliomyelitis -in 99.6-100% of children. Type b Haemophilus influenzae antibodies could be observed 1 month after the third administration of the vaccine in 92-100% of cases (according to different authors) [6][7][8][9].…”
mentioning
confidence: 99%
See 1 more Smart Citation